From Occupations to Embedded Skills : A Cross-Country Comparison - Aedo, Cristian (World Bank, Washington, D.C., 2013)
This paper derives the skill content of 30 countries, ranging from low-income to high-income ones, from the occupational structure of their economies. Five different skills are defined.. Cross-country measures of skill content show that the intensity of national production of manual skills declines with per capita income in a monotonic way, while it increases for non-routine cognitive and interpersonal skills. For some countries, the analysis is able to trace the development of skill intensities of aggregate production over time. The paper finds that although the increasing intensity of non-routine skills is uniform across countries, patterns of skill intensities with respect to different forms of routine skills differ markedly.